The Great Shadow - Doyle, Arthur Conan (Saga Egmont, 2022)
Originally published in 1892, 'The Great Shadow' is a story set during the Napoleonic war by world-famous author Sir Arthur Conan Doyle. Narrator Jack Colder reflects back on his life – from his rural, coastal upbringing on the Scottish-English border, through his boarding school years and ultimately to his participation in the Battle of Waterloo, one of the most infamous conflicts of all time. Full of suspense and danger, there is also time for romance in this gripping historical novel by the popular Sherlock Holmes author.-